Synthesis of silver decorated silica nanospheres for Surface Enhanced Raman Scattering (SERS) substrates - Ahmad Shaharuddin, Siti Shafiqah; Md. Nor, Roslan; Amin, Y.M; Bradley, David A. (Trans Tech Publications, 2016)
A sol-gel technique has been used to synthesize silver decorated silica nanospheres for Surface Enhanced Raman Scattering (SERS) substrates. X- Ray diffraction (XRD) spectra shows peak at 2θ = 38.1, 44.6, 64.7, and 77.5° confirming the presence of Ag nanoparticles on the substrates. The Ag decorated silica nanospheres were applied as SERS substrates using Rhodamine 6G (R6G) as probe molecule. From Raman analysis, the highest SERS enhancement factor is observed at R6G concentration of 102 mol L-1 calculated around ~109 .